2020
DOI: 10.1038/s41598-020-65536-6
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Roles of the JMJD1A Interaction Partners MDFI and MDFIC in Colorectal Cancer

Abstract: MyoD family inhibitor (MDfi) and MDfi domain-containing (MDfic) are homologous proteins known to regulate myogenic transcription factors. Hitherto, their role in cancer is unknown. We discovered that MDFI is up-and MDFIC downregulated in colorectal tumors. Mirroring these different expression patterns, MDFI stimulated and MDFIC inhibited growth of HCT116 colorectal cancer cells. Further, MDFI and MDFIC interacted with Jumonji C domain-containing (JMJD) 1 A, a histone demethylase and epigenetic regulator involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…Macartney-Coxson DP et al found that GFRA2 was remarkably down-regulated in the process of CRC and possibly related to liver metastasis [ 21 ]. In mice, the function inhibition of MyoD family inhibitor ( MDFI ) promotes the regeneration of the gastrocnemius muscle after injury [ 22 ]. In addition, MDFI is over expressed in CRC tumors and high expression of MDFI is associated with tumor metastasis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macartney-Coxson DP et al found that GFRA2 was remarkably down-regulated in the process of CRC and possibly related to liver metastasis [ 21 ]. In mice, the function inhibition of MyoD family inhibitor ( MDFI ) promotes the regeneration of the gastrocnemius muscle after injury [ 22 ]. In addition, MDFI is over expressed in CRC tumors and high expression of MDFI is associated with tumor metastasis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In mice, the function inhibition of MyoD family inhibitor ( MDFI ) promotes the regeneration of the gastrocnemius muscle after injury [ 22 ]. In addition, MDFI is over expressed in CRC tumors and high expression of MDFI is associated with tumor metastasis [ 22 ]. In this study, we found that down-regulated GFRA2 and up-regulated MDFI were differentially expressed-methylated genes in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…While overexpression of MDFI and MDFIC were observed in the brain, gastric and pancreatic tumors. This implicated that MDFI might perform tumor-promoting activities (Sui et al, 2020). Further investigation in colorectal cancer also showed that DNA methylation of MDF1 gene could be considered as an epigenetic biomarker in colorectal cancer (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…MDFIC also influences signal transduction pathways including the Wnt/β-catenin and JNK pathways [ 76 , 77 ]. MDFIC is epigenetically silenced in cancerous hematopoietic cell lines, suggesting it may function as a tumor suppressor [ 78 ], an idea supported by the observation that ectopic expression of MDFIC suppresses the growth of a colorectal cancer cell line [ 79 ]. Yet the impact of MDFIC on cancer cells may be cancer cell-specific, as MDFIC expression enhanced the chemoresistance of cancer stem cells in a lung cancer cell model [ 80 ].…”
Section: Resultsmentioning
confidence: 99%